Factors that influence the survival of unstable pelvic fracture in the acute phase (Medical Journal of Indonesia, 2018)
Background: The fatality rate of unstable pelvic fracture is still high (20–50%) due to acute phase hemorrhage or late multiple organ failure. The assurance for 100% survival in acute phase had been reported if the emergency room team have the right technique, right timing, and right protocol. The aim of this study was to evaluate and to date factors that influence the non-survival unstable pelvic fracture within 2x24 hours.Methods: This retrospective study was conducted in emergency unit of Dr. Soetomo General Hospital Surabaya during 2012–2016 for unstable pelvic fracture with unstable hemodynamic, without concomitant head or thoracic injury and admitted within 4 hours after the incident. All patients were handled according to the protocol for resuscitation and C-clamp insertion immediately. X-ray was taken after the insertion to check the C-clamp position and to confirm the diagnosis. The 2x24-hour data were taken whether the patient survive or not survive, including mean arterial pressure (MAP) pre-and post, heart rate (HR) pre-and post, and initial hemoglobin and platelet count. Data were analyzed with independent t-test and multiple regression analysis.Results: Twenty two patients were recorded as the inclusive criteria, separated into 17 survivors and 5 non-survivors. They were comprised of 14 males and 8 female patients, with an average of 31.9±15.3 years old. The MAP post, HR pre-and post, and platelet count were significantly different. The factor that influenced the survival within 2x24 hours was the MAP post C-clamp (>70 mmHg) (p<0.05).Conclusion: The acute phase 2x24-hour outcome after C-clamp insertion and resuscitation was significantly influenced by MAP post C-clamp and resuscitation.